2020
DOI: 10.1039/d0ta03555f
|View full text |Cite
|
Sign up to set email alerts
|

Probing electrochemical reactivity in an Sb2S3-containing potassium-ion battery anode: observation of an increased capacity

Abstract: Sb2S3–rGO potassium-ion battery anode material is synthesised by the peroxide route and is evaluated in two non-aqueous electrolytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Additionally, optimizing a suitable electrolyte is also beneficial to improving the performance of Sb-based PISs. Studies have found that different electrolytes are likely to have a diametrically opposite difference for the impact of the same material in K-storage [142]. As presented in Fig.…”
Section: Metallic Antimony For Potassium-ion Batteriesmentioning
confidence: 95%
See 2 more Smart Citations
“…Additionally, optimizing a suitable electrolyte is also beneficial to improving the performance of Sb-based PISs. Studies have found that different electrolytes are likely to have a diametrically opposite difference for the impact of the same material in K-storage [142]. As presented in Fig.…”
Section: Metallic Antimony For Potassium-ion Batteriesmentioning
confidence: 95%
“…Due to the similar reaction mechanism of PIBs and SIBs and the similar ionic radius of K + and Na + , many modification strategies for Sb-based materials (e.g., metal Sb, oxide, sulfide, selenide, and alloy) have been used to enhance their performance as the anodes of PIBs. However, the Sb-based materials have encountered obstacles as an anode in PIBs that are similar to those of SIBs; these obstacles can be overcome by several classic strategies, such as coupling carbon material, introducing heteroatom dopants, combining with other conductive substrates, synthesizing specific structures, and employing specific electrolytes and binders [131][132][133][134][135][136][137][138][139][140][141][142][143][144][145].…”
Section: Metallic Antimony For Potassium-ion Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…15f ). 93 When tested in a KIB cell, there was a high depotassiation capacity (633 mA h g −1 ) ( Fig. 15g ), and the reaction mechanism of the Sb 2 S 3 with potassium was also analyzed via post-cycling XRD and in situ transmission electron microscopy (TEM), thereby unveiling the presence of antimony alloys, potassium polysulphides, and a conversion–alloying reaction mechanism.…”
Section: Potassium Storage Chemistrymentioning
confidence: 99%
“…7 However, they are facing the challenges of low electronic and ionic conductivity as well as complicated phase change during K storage, which could lead to a large volume change, causing the pulverisation and delamination of the materials and even KIB cell failure. 36 It is worth pointing out that the conversion reaction of metal sulphides and selenides can cause the dissolution of K polysulphides/polyselenides in the electrolyte and trigger the shuttle effect, 15,[37][38][39] which results in rapid capacity fade and irreversible side reactions in the KIB cell.…”
Section: Challenges Of Electrode Materials In Kibsmentioning
confidence: 99%